Membongkar Mitos “Kehilangan Belajar” (Learning Loss) dengan Refleksi Diri - Slameto Slameto (Jurnal Basicedu, 2022)
Myth is not a lie. It is a belief that is adopted by people because it seems make sense, true, and consistent with at least some evidence. It is not true or at least not entirely true. However, until now people still believe in the myths about online learning, whatever they are, including learning loss. Online educational world is somewhat dominated by ridiculous myths; they are dangerous since they can retard positive changes in such world. There have been identified several myths which retard and even endanger online learning, especially learning loss as well as ways to prevent and critiques to them. Apparently, self-reflection is the key to break through the dangerous eight myths of learning loss. We believe that “corona children” or kids who were born during the covid-19 pandemic have learned much than the previous generation; they are more resilient, knowledgeable, creative, and have more potential than that of previous generation because things they have been through have given them more progress in many ways we might have never thought before. Thus, educators and policy makers are expected to be part of children’s learning facilitators in the new normal era, respect any learning places, and encourage places which facilitate students’ learning development.